2022
DOI: 10.1161/jaha.121.024249
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in International Cardiology Guideline Authorship: A Comparison of the US, Canadian, and European Cardiology Guidelines From 2006 to 2020

Abstract: Background Women continue to be underrepresented in cardiology and even more so in leadership positions. We evaluated the trends and gender differences in the guideline writing groups of the American College of Cardiology/American Heart Association (ACC/AHA), Canadian Cardiovascular Society (CCS), and European Society of Cardiology (ESC) guidelines from 2006 to 2020. Methods and Results We extracted all guidelines authors from 2006 to 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Significant gender inequity persists when it comes to compensation. Female cardiologists continue to earn, on average, $32,000 less than male cardiologists in both private practice and academia, even after controlling for location, subspecialty, and full-time status ( 65 , 66 , 69 ). This disparity in earnings is exacerbated by the cost of children, both in fewer work hours or hired child care: either women are predominantly responsible for looking after their children (and thus not able to work and earn), or they must arrange paid childcare, which will cost around 11–20% of their salary ( 44 , 53 , 56 ).…”
Section: Barriers To Entering and Remaining In The Cmr Fieldmentioning
confidence: 98%
See 1 more Smart Citation
“…Significant gender inequity persists when it comes to compensation. Female cardiologists continue to earn, on average, $32,000 less than male cardiologists in both private practice and academia, even after controlling for location, subspecialty, and full-time status ( 65 , 66 , 69 ). This disparity in earnings is exacerbated by the cost of children, both in fewer work hours or hired child care: either women are predominantly responsible for looking after their children (and thus not able to work and earn), or they must arrange paid childcare, which will cost around 11–20% of their salary ( 44 , 53 , 56 ).…”
Section: Barriers To Entering and Remaining In The Cmr Fieldmentioning
confidence: 98%
“…Women have significantly lower rates of the first authorship, particularly in high-impact journals, and are cited less often (60)(61)(62)(63). Female cardiologists are often neither involved in the high-impact trials nor on the writing committees of clinical guidelines (64)(65)(66). Women in academia also have less success in career development awards, with gender differences persisting in a number of awards for clinician-researchers in the US, even when adjusting for confounders (67).…”
Section: Academiamentioning
confidence: 99%
“…In this issue of the Journal of the American Heart Association (JAHA) , Rai et al report longitudinal trends in women authors of cardiology guidelines from 2006 to 2020. 2 The authors evaluated North American guidelines (from the American College of Cardiology/American Heart Association [ACC/AHA] and Canadian Cardiovascular Society) and European guidelines (from the European Society of Cardiology). From dozens of guidelines, findings revealed that among 1288 authors of ACC/AHA guidelines, 28% were women, whereas among 988 Canadian Cardiovascular Society authors, 26% were women, and among 1157 European Society of Cardiology authors, only 16% were women.…”
mentioning
confidence: 99%
“…4 More than half of cardiovascular trials in the last decade had a leadership structure entirely devoid of female physicians, and only 26% of cardiology practice guideline authors were women. 5 , 6 These statistics explain in large part our failures to effectively recruit representative study cohorts in our clinical trials and to equitably translate research advances into improved population health. The lack of representative data delays adoption of potentially life-prolonging or enhancing treatment strategies and inflicts harm when therapeutics are used without evidence of safety.…”
mentioning
confidence: 99%